PROFESSIONAL BURNOUT SYNDROME IN SOCIAL WORKERS, EMPLOYED IN COMMUNITY REHABILITATION CENTRES FOR ADDICTIVE DISEASES: THE CONTEXT OF INTERPERSONAL RELATIONSHIPS - Gudzinskiene, Vida; Pozdniakovas, Andrejus; Šinkūnienė, Jautre Ramute (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article overviews the problematic questions of the study: 1) What interpersonal factors cause professional burnout syndrome in social workers, employed in community rehabilitation centres for addictive diseases; 2) How communal relationships with colleagues can help overcome professional burnout. Research object: interpersonal relationships of social workers. The aim of the article is to reveal possibilities of overcoming professional burnout syndrome on the basis of the experiences of social workers’ interpersonal relationships. Research methods: academic literature analysis, document analysis, the method of a semi-structured interview, quality (content) analysis, summarizing method were used. The study was conducted in January – March of 2020 in the community rehabilitation centre for addictive diseases. Empirical research has shown that social workers, employed in community rehabilitation centres for addictive diseases, believe that the threat and risk of professional burnout syndrome arise, first of all, from interpersonal relationships with clients: their negative attitude towards social workers, inadequate client communication culture, lack of positive feedback. Secondly, it is important for social workers to feel emotional and moral support and help of colleagues, share responsibility for work. Joint leisure time improves the quality of communication between colleagues, strengthens the inner relationship in the collective, increases work efficiency.